The association between GAD1 gene polymorphisms and cerebral palsy in Chinese infants - Lin Sheyu; Li Tongchuan; Zhu Dengnan; Ma Caiyun; Wang Yinghong; He Lin; Zhu Changlian; Xing Qinghe (Цитология и генетика, 2013)
Studies suggest that GAD1 gene was a functional candidate susceptibility gene for cerebral palsy (CP). In order to investigate the contribution of GAD1 gene to the etiology of CP in Chinese infants, we carried out a case-control association study between GAD1 gene and CP. In this study, 374 health controls and 392 infants with CP were recruited. Genomic DNA was extracted from venous blood and all three single nucleotide polymorphisms in GAD1 (rs3791874, rs3791862 and rs16858977) were genotyped by Sequenom’s MassARRAY system. There were no significant differences in allele or genotype frequencies between CP or mixed CP patients and controls at any of the three genetic polymorphisms. Through haplotype analysis we found that haplotype GG (rs3791862, rs16858977) frequency demonstrated significantly statistical difference between mixed CP patients and controls (p= 0.0371). Our positive findings of haplotype GG suggested that variation of GAD1 gene was an important risk factor for mixed CP. Предполагается, что ген GAD1 является функциональным кандидатом на роль гена подверженности церебральному параличу (ЦП). Для исследования вклада гена GAD1 в этиологию ЦП у китайских детей методом случай – контроль проведено исследование ассоциации между наличием гена GAD1 и ЦП. В исследовании были задействованы 374 здоровых ребенка (контроль) и 392 ребенка с ЦП. Геномную ДНК выделяли из венозной крови, и все три единичных нуклеотидных полиморфизма гена GAD1 (rs3791874, rs3791862 и rs16858977) были генотипированы в системе Sequenom MassARRAY. Ни для одного из трех генетических полиморфизмов не обнаружено существенных различий в частотах аллелей или генотипов между больными ЦП или смешанными больными ЦП и контролем. Анализ гаплотипов показал существенные статистические различия в частоте гаплотипа GG (rs3791862, rs16858977) у смешанных больных ЦП и контрольной группы (p = 0.0371). Позитивный результат по гаплотипу GG свидетельствует о том, что вариация гена GAD1 является важным фактором риска для смешанного ЦП.